The use of living materials in teaching general botany - De Guzman, Francisco G. 1938- ([Quezon City s.n.], 1966)
The author cited the values and advantages of using living plant materials for instruction in relation to the objectives of science teaching. This study investigates the locations or habitats of common living plants used in General Botany Course, the practical methods of culturing the lower forms of plants, the laboratory exercises which utilize living plant specimens, and the living plant materials that are commonly used in demonstrating elementary biological principles.
Thesis (M.A.T.)--University of the Philippines
Keywords: Botany -- Study and teaching